The Effect of Social Networks on National Identity of the Students - Ghaemi, Ali; Khoddami, Alireza; Rasekh, Keramatollah (International Journal of Psychosocial Rehabilitation, 2020)
The study has aimed to investigate the effect of modern communicational technologies on national identity of the students in Islamic Azad University of Kerman. The methodology is survey and statistical population includes the students of Islamic Azad University of Kerman. The statistical sample has been calculated as 397, using Cochran formula. The findings of the study were obtained in two sections of descriptive statistics (frequency distribution, graph, mean and standard deviation) and inferential statistics using t-test for independent groups, correlation coefficient and regression coefficient in significance level of P